Health reform in China: Developments and future prospects - Jiwei Qian (Wiley, 2022)
Abstract In 2009, China initiated a new round of health reform to establish a well‐functioning health system. The 2009 health reform did make some significant achievements in improving affordability and accessibility. In particular, social health insurance has been expanded significantly and various social health insurance plans have covered over 95% of total population in China by 2011. The Chinese government also has significantly increased fiscal input for health financing. However, affordability remains a serious concern as the social health insurers, as purchasers, were not very effective in containing the growth of health expenditure. Accessibility to primary care and public health is another concern. In this context, health governance reforms are necessary to address affordability and accessibility issues. Health governance set rules for key actors of the health system (including service providers, health insurers and government departments) by taking into account the strategies and incentives of these actors in their interactions. In recent years, a series of reforms in health governance have been initiated. Some progresses have been achieved. For the next stage of health reform, issues including how to further reform the governance structure of medical institutions and how to improve resource allocation in the health system are critical.